PENGUJIAN ANTIBAKTERI BEDAK DINGIN HERBAL MAHKOTA DEWA TERHADAP BAKTERI PENYEBAB JERAWAT - Yosy Silalahi; Indah Sari; Surianto Siregar; Dewi Rani Sinaga; Meliza Matari (Jurnal Farmanesia, 2016)
The fructus of Mahkota dewa (Phaleria macrocarpa) fructus contains alkaloids,Â saponins, tannins and flavonoids that function as an antioxidant. In this study, its fructus is used as a main ingredient for this powder formulation that is combined with various other traditional crops. The aim of this research is to make a formula of a tradisional powder as an antibacterial from acne (P. acne). The method used in this research is the Minimum Inhibitory Concentration Test (MIC) and Total Plate CountTest. The MIC results of this research that of the Phaleria extract capableof inhibiting the growth of P.acne is 3% with inhibition zone diameter of 0.8 cm. And the result of Total Plate Count Test for yeast is 9.0 x 10 3 andforbacteria is 17.5 x 105.